2008
DOI: 10.1111/j.1462-5822.2008.01188.x
|View full text |Cite
|
Sign up to set email alerts
|

Dectin-1 synergizes with TLR2 and TLR4 for cytokine production in human primary monocytes and macrophages

Abstract: SummaryThe b-glucan receptor dectin-1 and Toll-like receptors TLR2 and TLR4 are the main receptors for recognition of Candida albicans by the innate immune system. It has been reported that dectin-1 amplifies TLR2-dependent induction of cytokines in mouse models. In the present study we hypothesized that dectin-1 has potent synergistic effects with both TLR2 and TLR4 in human PBMCs and macrophages. Human PBMCs and monocyte-derived macrophages were stimulated with curdlan, a linear b-1,3-glucan-polymer derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
248
0
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 306 publications
(269 citation statements)
references
References 47 publications
(59 reference statements)
16
248
0
5
Order By: Relevance
“…This is important because it has been welldescribed that ''cross-talk'' between the TLR2/4 and Dectin-1 is responsible for the synergy of proinflammatory response mounted by the host [32][33][34]. Our use of pure TLR2, TLR4, and Dectin-1 ligands, as well as TLR2/Dectin-1 and TLR4/Dectin-1 ligand combination, illustrated the profound influence that 1,25(OH) 2 D 3 exerted beyond its effect on the individual PRR.…”
Section: Discussionmentioning
confidence: 99%
“…This is important because it has been welldescribed that ''cross-talk'' between the TLR2/4 and Dectin-1 is responsible for the synergy of proinflammatory response mounted by the host [32][33][34]. Our use of pure TLR2, TLR4, and Dectin-1 ligands, as well as TLR2/Dectin-1 and TLR4/Dectin-1 ligand combination, illustrated the profound influence that 1,25(OH) 2 D 3 exerted beyond its effect on the individual PRR.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was first revealed that MCP-1 was produced through Dectin-1-mediated signal transduction by using curdlan, a specific agonist of Dectin-1, in mast cells in a TLR2-independent manner (Fig. 6B) (52,53). IL-4 and IL-13, canonical type 2 cytokines, are closely related cytokines required for the generation of high-affinity IgE antibodies, mucus overproduction, and smooth muscle alterations (54).…”
Section: Discussionmentioning
confidence: 99%
“…Recent data suggest that glycan-induced CLR signaling can modulate inflammatory responses by enhancing or suppressing TLR-mediated responses (59,60). Especially the C-type lectin DC-SIGN shows interesting properties that are often, but not always, associated with Th2 polarization, suppression of inflammation and induction of a regulatory function (61)(62)(63).…”
Section: Can Helminth Compounds Suppress Inflammatory Responses Of DCmentioning
confidence: 99%